Effect Of Earnings Management, Leverage, And CSR On Tax Avoidance With GCG As Moderating Variable - Wulandari Hidayanti; Tantina Haryati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to test and analyze the effect of Earning management, leverage, and CSR on Tax avoidance with moderated by independent commissioners for GCG. Property and real estate companies are the population used in this study, where the processed companies are companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Quantitative approach is used in research”using secondary data in the form of financial statements”for 2018-2022. The purposive sampling method is one of the methods used for research, from this method researchers get 15 real estate companies as research samples. This study uses partial least squares (PLS) and SmartPLS 3. The results of this study indicate that earnings management and leverage have no significant impact on tax avoidance. GCG is unable to moderate Earning Management, Leverage, and CSR on Tax Avoidance because the P-Values are less than 0.5%. While Corporate Social Responsibility has a significant effect on Tax Avoidance because the P-Values are greater than 0.5%. The results of this study can be good input to the government or companies in the best possible taxation practices, so that practices that utilize tax avoidance can be used.